Implementasi Teknologi Pengusir Burung Otomatis untuk Petani Padi Desa Muntang - Muhammad Panji; Nur Afifah Zen; Prasetyo Yuliantoro; Shinta Romadhona; Dodi Zulherman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Farmers in Muntang Village, Kemangkon, Purbalingga, face substantial crop losses due to bird attacks during the ripening stage of rice cultivation. Conventional deterrents such as scarecrows and hanging cans have become ineffective as birds have adapted to their static nature. This community engagement initiative implements an automatic, solar-powered bird-repellent system combining ultrasonic sensors, servo-driven mechanical noise elements, and electronic buzzers. The stages included system design, component procurement, device assembly, field installation, farmer training, and performance evaluation. Two units were successfully deployed in the rice fields, demonstrating effective responses to bird movement. More than twenty farmers participated in hands-on training and increased their understanding of appropriate agricultural technology. Initial field observations indicated reduced bird intrusion, improved crop protection, and enhanced labor efficiency. This initiative contributes to food security at the village level and supports the adoption of simple smart-farming innovations in rural agricultural settings.